System pathogens inhibiting construction project risk management performance: deliberate ignorance perspective - Ekung, Samuel Bassey; Adu, E.; Lashinde, A. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Risks have emerged as one of the most significant project management concerns due to their effects on construction project performance. Several literature attributes the increasing consequences of risks to low awareness and ineffective management practices. This paper draws attention to the existence of latent pathogens affecting the efficiency of risk management performance (RMP). The objective was to determine whether construction stakeholders’ ‘deliberate ignorance’ of inherent risk management pathogens classified as complexity, complicatedness, mindlessness, and project pathologies affects RMP. A survey questionnaire administered to 135 certified construction project managers in Nigeria provided the data used for the study. Data analysis engaged descriptive statistics and Fuzzy Set Theory. The result revealed that ineffective RMP arise mainly from factors related to project complexity and mindlessness. Complexity increases project uncertainty without appropriate tools to address them; while the criticality of the relationships between risks elements continuously vary in practice. Mindlessness depicts stakeholders’ ‘wilful ignorance’, biased perception, and mind-set towards risk management. The results suggest that reducing project complexity, biased perceptions and improving stakeholders’ capacity would benefit RMP. Therefore, improving the capacity of stakeholders and developing appropriate tools to address the changing nature of risks are areas to improve RMP.